Techniques for hot embossing microstructures on liquid silicone rubbers with fillers. (November 2015) - Vudayagiri, Sindhu; Yu, Liyun; Skov, Anne Ladegaard
Embossing is an established process for the thermoplastic elastomers but not yet for the thermosetting elastomers. It has already been shown that hot embossing is a viable technology for imprinting microstructures in addition to curing thin silicone films at their gel point. It is one of the simplest, most cost-effective, and time-saving methods for replicating microstructures. In the present study, films made from liquid silicone rubber (LSR) formulations containing fillers are hot embossed under modified operating conditions. The use of such relatively hard silicone elastomers shows the versatility of this method that has been established for softer silicone elastomers. Also, as a proof of concept, a microstructured metal (nickel (Ni)) plate is used as an embosser for the films successfully. The ideal condition for hot embossing the LSR formulation (XLR 630 with titanium dioxide fillers) with a Ni embosser is 110°C preheating for 15–35 s, embossed with 2 bar pressure, and postheating for complete curing at 110°C for 3 min showing that the process is extremely fast.